Dampak Pemberian Reward and Punishment Untuk Meningkatkan Kedisiplinan Anak Usia Dini - Arinalhaq, Ririen; Eliza, Delfi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Discipline is a concept that must be instilled from an early age. How to teach discipline to children at the age of 3-6 years is usually taught in simple things such as tidying up toys, accepting consequences for doing wrong or right, obeying the guidance of parents around, and others. Education aims to train children so that children can be responsible and can realize if there are mistakes they have made. Reward and punishment is an effective way to teach discipline to children. This article aims to describe or conceptually describe the application of reward and punishment to early childhood to train discipline. The method used is a literature study or literature study which contains the opinions of various experts regarding a particular problem which is then examined, compared with the research and researchers who draw conclusions. In this article, the author only analyzes two of them. Several findings from previous studies illustrate that offering these rewards and punishments can improve discipline in children in various ways, such as giving stars, giving praise, giving hand flour, and others. The conclusion of this article is that with reward and punishment, children can better control their emotions and obey the rules that have been given by teachers and parents.